Pengaruh Citra Merek dan Kualitas Produk terhadap Keputusan Pembelian Laptop merek Asus di Tenggarong - Wildan, Muhammad Wildan; Wijayanti, Silvana Kardinar; Hendra (I-Con Media, 2024)
This study entitled The Effect of Brand Image and Product Quality on Purchasing Decisions for Asus brand laptops aims to determine the effect of brand image on purchasing decisions, the effect of product quality on purchasing decisions and the effect of brand image and product quality on purchasing decisions for Asus brand laptops. This study uses two independent variables, namely brand image and product quality and one dependent variable, namely purchasing decisions. The data in this study were collected through distributing questionnaires to 100 Tenggarong people who used Asus brand laptops as research samples. The sampling technique used was purposive sampling. Based on data analysis, the results showed that the indicators in this study were valid and reliable. In the classical assumption test, the data is normally distributed, there is no heteroscedasticity and multicollinearity. In the hypothesis test in the t test it is known that the brand image variable has a significant effect on purchasing decisions, the product quality variable also has a significant effect on purchasing decisions. In the F test it is known that brand image and product quality have a joint effect on purchasing decisions. In the R2 test, it is known that the magnitude of the influence of brand image and product quality on purchasing decisions is 87.8%. While the remaining 12.2% is influenced by other factors outside the brand image and product quality variables.